# Let f(x) = 9x − 2 and g(x) = - x + 3. Find f(g(x)).

- 9x - 2, - 9x + 5, - 9x + 25, - 9x + 27

**Solution:**

The f(g(x)) shows the composite function when the function g(x) is substituted in the function f(x) and simplified.

Step 1: Substitute g(x) into f(x) that is x = - x + 3.

f(g(x)) = 9(- x + 3) − 2

Step 2: Simplify the equation to get the value.

f(g(x)) = - 9x + 27 − 2

f(g(x)) = - 9x + 25

## Let f(x) = 9x − 2 and g(x) = - x + 3. Find f(g(x)).

- 9x - 2, - 9x + 5, - 9x + 25, - 9x + 27

**Summary: **

The value of f(g(x)) is - 9x + 25.